PENGGUNAAN MEDIA PEMBELAJARAN AUDIOVISUAL PREZI PADA MATERI TEKANAN ZAT CAIR DI KELAS VIII SMP PGRI 1 PALOH - Meiliana Sari; Tomo Djudin; Muhammad Musa Syarif Hidayatullah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the effect of using Prezi learning media on the results of class VIII student on the material of liquid pressure. This research was conducted at SMP PGRI 1 Paloh. The method of research used was an experiment with a preprogrammed posttest using paired sample t-test and an independent sample t-test. The sample in this study was classroom VIII A as an experimental class using Prezi learning media and VIII B using powerpoint as control class. The test in this study was a matter of 5 essay. According to data analysis guidelines, concluded (1) There is an increase in student learning outcomes after applying Prezi learning by 58.62 with an N-gain score of 0.33 and learning using powerpoint by 51.14 with an N-gain score of 0.26 ( 2) There are differences in student learning outcomes before and after being given learning that uses Prezi (p < 0.05) and learning that does not use Prezi (p < 0.05) by testing the difference in the average score of learning outcomes for the experimental class and the control class. obtained p = 0.04 < 0.05 (3) The use of Prezi learning media is effectively used in the learning process with an effect size value (ES = 0.46) effectiveness in moderate criteria.Keywords: Prezi learning media, results of learning, liquid pressure